Modifikasi Pati Jagung (Zea mays) secara Heat Moisture Treatment (HMT) untuk Memperbaiki Sifat Fisik dan Mekanis Edible Film - Islamawan, Praboyo Ardin; Purnomo, Eko Hari; Wulandari, Nur (Jurnal Teknologi dan Industri Pangan, 2025)
Plastic production is already high, and plastic pollutes the environment after use. There is a need for innovation in food packaging, such as the use of edible films as an alternative to reduce the use of plastic materials. Edible films can be prepared from starch. In Indonesia, starch-producing plants are abundant and among them such as potatoes, cassava, rice and corn have the potential to be used for edible film production. The objective of this research was to improve the physical and mechanical properties of edible films by heat moisture treatment (HMT) modification of corn starch as a raw material. This research consisted of two stages: (1) characterization and modification of corn starch with three temperature treatments (HMT 100, 110, and 120 °C) and (2) characterization of the physical and mechanical properties of edible films. The results showed that The highest amylose content for HMT 120 treatment was 29.47% with a whiteness index of 84.40. The ap-pearance of starch granules after modification was different from the control, and the pasting properties para-meters such as maximum viscosity, trough viscosity, breakdown viscosity, final viscosity, and setback viscosity of starch after modification were below those of the control. Edible films had an average thickness of 0.14 mm, while transparency was different from the control, with the lowest value on HMT 100 was 1.11. HMT 120 sample had the best characteristics with the lowest WVTR value of 23.47 g/m2/24 h, and the highest tensile strength value of 4.12 MPa, while the elongation value was similar to other samples and control. HMT 120 had a highest value on X-ray diffraction XRD with a degree of crystallization up to 41%. The modification of HMT has the potential to improve the characteristics of edible films, both in terms of properties and mechanics.